Dysplasia Risk in Ileal Pouches after Reconstructive Surgery for Ulcerative Colitis - Hugh J Freeman (Canadian Journal of Gastroenterology)
An important goal for the surgeon after performing proctocolectomy for ulcerative colitis is the preservation of continence, with the formation of a pelvic ileal pouch. In most patients who have required this procedure, clinical results have been satisfactory. In recent years, it has become appreciated that many patients with a satisfactory surgical result are still at risk for pouchitis and pouch neoplasia. This is not surprising because creation of a pouch leads to an environment characterized by stasis, with associated mucosal adaptive changes. In some patients, the ileal mucosa in the pouch may assume the appearance of colonic mucosa.